Vortex fluidics mediated non-covalent physical entanglement of tannic acid and gelatin for entrapment of nutrients. Issue 3 (8th January 2021) - Cao, Xuejiao; Joseph, Nikita; Jellicoe, Matt; Al-Antaki, Ahmed Hussein Mohammed; Luo, Xuan; Su, Dongxiao; He, Shan; Raston, Colin
Abstract : We have developed a simple process for the entrapment of nutrients in shear stress induced non-covalent physically entangled tannic acid-gelatin gel in a thin film vortex fluidic device (VFD) operating under continuous flow. Abstract : We have developed a simple process for the entrapment of nutrients in shear stress induced non-covalent physically entangled tannic acid-gelatin gel in a thin film vortex fluidic device (VFD) operating under continuous flow. This allows control of the porosity and surface area of the pores in order to improve the nutrient entrapment capacity. The VFD microfluidic platform simplifies the processing procedure of physically entangled biopolymers, as a time and cost saving one-step process devoid of any organic solvents, in contrast to the conventional homogenization process, which is also inherently complex, involving multiple-step processing. Moreover, the use of homogenization (as a benchmark to entrap nutrients) afforded much larger porosity and surface area of pores, with lower entrapment capacity of nutrients. Overall, the VFD processing provides a new alternative, bottom-up approach for easy, scalable processing for materials with a high nutrient entrapment capacity.